2012
DOI: 10.1071/rd11068
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of pluripotency and differentiation-related markers in cat oocytes and preimplantation embryos

Abstract: During mammalian preimplantation development, two successive differentiation events lead to the establishment of three committed lineages with separate fates: the trophectoderm, the primitive endoderm and the pluripotent epiblast. In the mouse embryo, the molecular mechanisms underlying these two cell fate decisions have been studied extensively, leading to the identification of lineage-specific transcription factors. Species-specific differences in expression patterns of key regulatory genes have been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 77 publications
1
35
0
Order By: Relevance
“…), RT‐qPCR has become the method of choice also for very tiny sample sizes, such as single embryos (Filliers et al. ). However, the procedure of expression normalization varies and merits examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…), RT‐qPCR has become the method of choice also for very tiny sample sizes, such as single embryos (Filliers et al. ). However, the procedure of expression normalization varies and merits examination.…”
Section: Discussionmentioning
confidence: 99%
“…Filliers et al. () validated a set of reference genes, whose expression was found to be stable. The disadvantage of that method is that much of the valuable sample material has to be used for reference gene amplification and fewer genes of interest can be analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it has been reported that in vitro culture conditions can lead to increased incidence of cellular stress and apoptosis [15, 16] and induce aberrant DNA methylation in mouse embryos [17, 18], both of which may result in decreased blastocyst quality and even affect the viability of offspring after transfer into a surrogate. Gene expression analysis, a preferred method over conventional criteria like embryo morphology and developmental rates [19], has commonly been used to assess embryo quality and to optimize in vitro culture conditions [20]. Therefore, in this study, a group of marker genes related to cellular stress and apoptosis, and DNA methylation were measured to explore the regulatory mechanism of baicalin in developmental competence of mouse embryos in vitro .…”
mentioning
confidence: 99%
“…In feline species, expression analysis of genes associated with embryo development has become an important tool to understand the physiological response of embryos to their in vitro culture environment [24,25,26]. Though information for several genes has been provided, the change in gene expressions associated with stress-induced apoptosis is not entirely known in this species.…”
mentioning
confidence: 99%